Tryptophan supplementation and the response to unfairness in healthy volunteers - Cerit, Hilâl; Schuur, Rachel J.; de Bruijn, Ellen R. A.; Van der Does, Willem (Frontiers in Psychology, 2015)
Experimental manipulation of serotonin (5-HT) availability has been shown to modulate social behavior. For instance, serotonin depletion increased the rejection rates of unfair offers in the Ultimatum Game (UG), whereas a single dose of the serotonin reuptake inhibitor (citalopram) decreased rejection rates. These effects were observed immediately after the manipulation. The aim of this study was to investigate the effect of prolonged Tryptophan (TRP) supplementation on UG performance in healthy individuals. A randomized double-blind placebo-controlled design was used. Healthy volunteers (N=47) completed the UG before and after a 6-day intervention of TRP (2.8 g/day) or placebo. Impulsivity was measured with a Go-Stop task. The overall analyses showed that TRP supplementation had no significant effect on UG scores, but the direction of the effect was opposite from expectations. Because repeated performance of the UG may lead to unwanted learning effects or strategical changes, additional analyses were conducted in which participants (N=7) who accepted all offers on the second measurement were excluded. These analyses revealed that the TRP-group rejected very unfair offers more often than the placebo group. The groups did not differ on impulsivity. Increasing serotonin through TRP supplements increased the rejection of very unfair offers. The direction of our findings is inconsistent with earlier studies that showed that increasing 5-HT availability results in less rejection of unfair offers. The current findings thus importantly suggest that effects of acute vs. prolonged enhancement of 5-HT availability may differ. Also, the outcomes show that the UG is a complex task and participants’ decisions may depend on context, e.g., prior experience with the task.